Application of Artificial Bee Colony Algorithm and Finite Element Analysis for Optimum Design of Brushless Permanent Magnet Motor - Ilka, Reza; Gholamian, Seyyed Asghar (IIUM Engineering Journal, 2012)
ABSTRACT: This paper develops a mathematical relationship for the purpose of designing and selecting the optimum dimensions of a brushless permanent magnet motor. The design is optimised by the use of artificial bee colony algorithm with the goal of maximizing the power density and efficiency of the motor. The required dimensions of the brushless motor are calculated based on the optimum power density and efficiency requirements. Finally, the predicted results of the optimisation are validated using a 2-D numerical program based on finite element analysis. ABSTRAK: Kajian ini mencadangkan persamaan yang menghubungkan rekabentuk dan dimensi magnet motor kekal tanpa berus. Rekabentuk optima berdasarkan algorisma koloni lebah tiruan dengan tujuan meningkatkan ketumpatan kuasa dan keberkesanan dibentangkan dalam kajian ini. Dimensi magnet motor kekal tanpa berus dihitung dengan ketumpatan kuasa optima dan keberkesanan. Akhirnya, keputusan telah disahkan dengan menggunakan program berangka 2-D berdasarkan analisis elemen finit. KEYWORDS: brushless; permanent magnet motor; power density; artificial bee colony; algorithm; finite element analysis